Portal hyperflow in patients with hepatosplenic mansonic schistosomiasis - Cleva, Roberto de; Saad, William Abrão; Herman, Paulo; Pugliese, Vincenzo; Zilberstein, Bruno; Laudanna, Antonio Atílio; Gama-Rodrigues, Joaquim José (Revista do Hospital das Clínicas, 2004)
PURPOSE: The purpose of this study was to assess portal hemodynamics in patients with portal hypertension due to hepatosplenic schistosomiasis as well as to assess the contribution of splanchnic hyperflow to the pathophysiology of the portal hypertension. METHODS: Sixteen patients with schistosomal portal hypertension and previous history of upper digestive bleeding due to esophageal varices rupture underwent elective esophagogastric devascularization and splenectomy and were prospectively studied. All patients underwent intraoperative invasive hemodynamic portal monitoring with a 4F-thermodilution catheter. The intraoperative portal hemodynamic assessment was conducted after laparotomy (initial) and after esophagogastric devascularization (final). RESULTS: The initial portal pressure was elevated (mean 28.5 ± 4.5 mm Hg), and a significant drop of 25% was observed at the end of the surgery (21.9 ± 4.9 mm Hg). The initial portal flow was elevated (mean 1766.9 ± 686.6 mL/min). A significant fall (42%) occurred at the end of the surgical procedure (1025.62 ± 338.7 mL/min). Fourteen patients (87.5%) presented a portal flow of more than 1200 mL/min, and in 5 cases, values greater than 2000 mL/min were observed. CONCLUSIONS: Esophagogastric devascularization and splenectomy promote a significant reduction of the elevated portal pressure and flow in schistosomal portal hypertension. These data favor the hypothesis of portal hyperflow in the physiopathology of portal hypertension of schistosomiasis.